Dynamic fetal cardiac magnetic resonance imaging in four‐chamber view using Doppler ultrasound gating in normal fetal heart and in congenital heart disease: comparison with fetal echocardiography. (3rd May 2019) - Tavares de Sousa, M.; Hecher, K.; Yamamura, J.; Kording, F.; Ruprecht, C.; Fehrs, K.; Behzadi, C.; Adam, G.; Schoennagel, B. P.
ABSTRACT: Objectives: To investigate the diagnostic performance of dynamic fetal cardiac magnetic resonance imaging (MRI), using a MR‐compatible Doppler ultrasound (DUS) device for fetal cardiac gating, in differentiating fetuses with congenital heart disease from those with a normal heart, and to compare the technique with fetal echocardiography. Methods: This was a prospective study of eight fetuses with a normal heart and four with congenital heart disease (CHD), at a median of 34 (range, 28–36) weeks' gestation. Dynamic fetal cardiac MRI was performed using a DUS device for direct cardiac gating. The four‐chamber view was evaluated according to qualitative findings. Measurements of the length of the left and right ventricles, diameter of the tricuspid and mitral valves, myocardial wall thickness, transverse cardiac diameter and left ventricular planimetry were performed. Fetal echocardiography and postnatal diagnoses were considered the reference standards. Results: Direct cardiac gating allowed continuous triggering of the fetal heart, showing high temporal and spatial resolution. Both fetal cardiac MRI and echocardiography in the four‐chamber view detected pathological findings in three of the 12 fetuses. Qualitative evaluation revealed overall consistency between echocardiography and MRI. On both echocardiography and MRI, quantitative measurements revealed significant differences between fetuses with a normal heart and those with CHD with respect to the length of the right ( P  < 0.01 for both) and left ( P  < 0.01 for both) ventricles and transverse cardiac diameter ( P  < 0.05 and P  < 0.01, respectively). Tricuspid valve diameter on cardiac MRI was found to be significantly different in healthy fetuses from in those with CHD ( P  < 0.05). Conclusions: For the first time, this study has shown that dynamic fetal cardiac MRI in the four‐chamber view, using external cardiac gating, allows evaluation of cardiac anatomy and diagnosis of congenital heart disease in agreement with fetal echocardiography. Dynamic fetal cardiac MRI may be useful as a second‐line investigation if conditions for fetal echocardiography are unfavorable. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.